Minimum Wage and Firm Variety - Priyaranjan Jha; Antonio Rodríguez López (Center for Economic Studies and ifo Institute (CESifo), 2021)
Exploiting minimum-wage variation within multi-state commuting zones, we document a negative relationship between minimum wages and firm variety in the U.S. restaurant and retail-trade industries. To explain this finding, we construct a heterogeneous-firm model with a monopsonistic labor market and endogenous firm variety. The decentralized equilibrium underprovides the mass of firms compared to the outcome achieved by a welfare-maximizing planner. A binding minimum wage further reduces the mass of firms, exacerbating the distortion. Workers value employer variety, and thus, by reducing firm variety the minimum wage reduces workers' welfare even if the average wage increases.
Keywords: J38; J42; 330; minimum wage; number for firms; love of employer variety